Examination of the production of an isotensor dibaryon in the pp -> pp pi(+)pi(-) reaction - Adlarson, P.; Augustyniak, W.; Bardan, W.; Bashkanov, M.; Bergmann, F. S.; Berlowski, M.; Bondar, A.; Buescher, M.; Calen, H.; Ciepal, I.; Clement, H.; Czerwinski, E.; et al. (Physical Review C - Nuclear Physics, 2019)
The quasifree pp -> pp pi(+)pi(-) reaction has been measured by means of pd collisions at T-p = 1.2 GeV using the WASA detector setup at COSY enabling exclusive and kinematically complete measurements. Total and differential cross sections have been extracted for the energy region T-p = 1.08-1.36 GeV (root s = 2.35-2.46 GeV) covering thus the regions of N* (1440 ) and Delta(1232)Delta(1232) resonance excitations. Calculations describing these excitations by t-channel meson exchange as well as isospin relations based on the pp -> pp pi(0)pi(0) data underpredict substantially the measured total cross section. The calculations are also at variance with specific experimental differential cross sections. An isotensor Delta N dibaryon resonance with I(J(P)) = 2(1(+) ) produced associatedly with a pion is able to overcome these deficiencies. Such a dibaryon was predicted by Dyson and Xuong [Phys. Rev. Lett. 13, 815 (1964)] and more recently calculated by A. Gal and H. Garcilazo [Nucl. Phys. A 928, 73 (2014)].
CRIS-Team WoS Importer:2019-02-21